Pengaruh Konflik Peran Ganda, Pengalaman Kerja dan Kepribadian Terhadap Kinerja Perawat Wanita Rumah Sakit Dirgahayu Samarinda - Dewi Isna Laili; Tetra Hidayati; Dirga Lestari (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this research was to determine the effect of dual role conflict, work experience and the personality of the employees. This  Research was conducted on Dirgahayu Hospital Samarinda. Determinants of the sample by using purposive sampling with the total population 311 peopleand samples collected as many as 69 respondents that is on Dirgahayu Hospital Samarinda. Data from this research using primary data, interviews and questionnaires. Hypothesis test used in this research is Multiple Linear Regression using SPSS  21 version. These results indicate that: 1) Dual Role Conflict make a significant negative effect on the performance of female nurses in Dirgahayu Hospital Samarinda. 2) Work experience make a positive and significant impact on the performance of female nurses in Dirgahayu Hospital Samarinda. 3) Personalitymake a positive and significant impact on the performance of female nurses in Dirgahayu Hospital Samarinda.